2019
DOI: 10.1111/phn.12582
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of multidrug‐resistant tuberculosis in China: A meta‐analysis

Abstract: Background Multidrug‐resistant tuberculosis (MDR‐TB) brings major challenges to the health care workers (HCWs). This study is to determine the risk factors for MDR‐TB, latent tuberculosis infection (LTBI), and tuberculosis (TB) disease among HCWs in China. Methods A meta‐analysis was conducted to evaluate the risk factors for MDR‐TB, LTBI, and TB disease among HCWs using a random‐effects model, and the pooled odds ratios (ORs) with 95% confidence interval (CI) were used as effect indicators. Results We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Cavitary tuberculosis is caused by lung injury, and reflects macroscopic openings developed between the infection site and the airways that promote bacterial expectoration [ 50 ]. These cavities may remain for a long time in case of inappropriate treatment; cavity wall thickening might occur, as well as fibrotic lesions, which may progress to chronic fiber cavity pulmonary TB [ 8 ]. Drugs administered orally or intravenously rarely achieve effective circulating concentrations in cavities, promoting MDR occurrence [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cavitary tuberculosis is caused by lung injury, and reflects macroscopic openings developed between the infection site and the airways that promote bacterial expectoration [ 50 ]. These cavities may remain for a long time in case of inappropriate treatment; cavity wall thickening might occur, as well as fibrotic lesions, which may progress to chronic fiber cavity pulmonary TB [ 8 ]. Drugs administered orally or intravenously rarely achieve effective circulating concentrations in cavities, promoting MDR occurrence [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retreatment, RR-TB and EPTB are negative factors affecting the treatment outcome and prognosis of patients. Previous treatment history has been a well-known risk factor associated with drug-resistant TB including RR-TB 21 23 . Our result that patients between 21 and 40 years of age had higher odds of being RR-TB compared to those 20 years and younger was consistent with past studies 21 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…China has the second highest incidence of MDR/RR-TB, accounted for 14% of global MDR/RR-TB patients [1]. A meta-analysis about risk factors of MDR-TB in China showed that Han ethnic group, history of tuberculosis treatment, pulmonary cavity, migrant population, TB case contact history, living in rural areas and low income were considered to be at risk of MDR-TB [27,28]. In Golmud city, 40% previously treated cases are MDR/RR-TB.…”
Section: Discussionmentioning
confidence: 99%